Skill-based technology adoption: Firm-level evidence from Brazil and India - Rupert Harrison (Institute for Fiscal Studies (IFS), 2008)
This paper provides the first firm-level econometric evidence on the skill-bias of ICT in developing countries using a unique new dataset of manufacturing firms in Brazil and India. I use detailed information on firms' adoption of ICT and the educational composition of their workforce to estimate skill-share equations in levels and long differences. The results are strongly suggestive of skill-biased ICT adoption, with ICT able to explain up to a third of the average increase in the share of skilled workers in Brazil and up to one half in India. I then use variation in the relative supply of skilled workers across states within each country to identify the skill-bias of ICT. The results are again consistent with skill-bias in both countries, and are mainly robust to various methods of controlling for unobserved heterogeneity across states. The magnitudes of the estimated effects from both approaches are surprisingly similar for the two countries. Overall, the results suggest that new developments in ICT are diffusing rapidly through the manufacturing sectors of both Brazil and India, with similar implications for the demand for skills in two very different and geographically distant countries. This evidence is consistent with ongoing pervasive skill-biased technological change associated with ICT throughout much of the developed and developing world. The implications for future developments in inequality both within and between countries are potentially far-reaching.
Keywords: J2; O14; O33; 330; Informationstechnik; Technologiewahl; Qualifikation; Bias; Brasilien; Indien